Kepemimpinan transformasional dan green human resource management dalam mempengaruhi turnover intention: Peran kepuasan kerja sebagai variabel mediasi - Wibowo, Frendy; Susilowati, Eny; Setiyawan, Adi Andika; Hutomo, Chandra Wisnu (Nur Science Institute, 2025)
This study analyzes transformational leadership and green human resource management on turnover intention and job satisfaction as mediating variables at Risky Amalia Hospital, Sragen. This study uses a quantitative approach with data collection in the form of a survey. The research sample was 162 respondents: directors, medical services, nursing, support services, and finance and general. The sampling technique used purposive sampling, and the hypothesis model was tested with the Partial Least Square Structural Equation Modeling (Smart Pls) analysis tool. The findings show that transformational leadership and green human resource management have a positive and significant effect on job satisfaction and a negative effect on turnover intention. While job satisfaction significantly mediates between transformational leadership and green human resource management on turnover intention.